043 Admission MR-PROANP levels are superior to grace score and NT-PROBNP for risk stratification in non ST-elevation acute coronary syndromes. (22nd September 2015) - Dhillon, O S; Khan, S Q; Narayan, N H; Ng, K H; Struck, J; Quinn, P A; Morgenthaler, N G; Squire, I B; Dvaies, J E; Bergmann, A; Ng, L L
Abstract : Introduction: Endorsed by international guidelines, risk stratification plays a central role in the optimal management of patients with non ST-elevation (NSTE-ACS). High risk patients benefit from an early invasive approach and admission biomarker levels may help to identify this cohort. Atrial natriuretic peptide (ANP) is a recognised prognostic marker in ST elevation myocardial infarction (STEMI) and in heart failure (HF) but has not been evaluated in NSTE-ACS. The precursor of ANP is N-terminal Pro-ANP whose mid regional epitope is more stable when compared to epitopes of N- or C- terminals of pro-ANP used in previous assays. Aims: To assess the prognostic value, optimum time for sampling and a cut off value for mid regional proANP in unselected patients' with non ST elevation ACS (NSTE-ACS). We use GRACE risk score and NTproBNP as benchmark comparators. Method and Results: Plasma MRproANP was measured both on admission (taken within 36 h of symptoms) and discharge (3 to 5 days later) in 630 (437 men, median age 70.0±12.8 years) patients with NSTE-ACS. During follow up which ranged from 150 to 1059 days the primary end point of a major adverse cardiac event (MACE) was reached by 170 (27%) patients. This included 84 (13.3%) deaths, 56 (8.9%) readmissions with HF and 68 (10.8%) re-infarctions. Admission and discharge levels were entered into 2 separate multivariate Cox regression models adjusted for important clinical and biochemical factors and Receiver Operator Characteristic (ROC) analyses performed with results shown in Abstract 43 Table 1 . Admission levels demonstrated a stronger association with MACE were therefore used for comparison against GRACE score and admission NTproBNP level in a further multivariate Cox model. This showed that MRproANP (HR 5.81 p<0.001) and GRACE score calculated pre-discharge (HR 1.01 p=0.024) continued to be independently associated with the primary end point but not admission NTproBNP (HR 1.00 p=0.99) or GRACE score if calculated on presentation (HR 1.01 p=0.057). The accuracy of MRproANP at prediction of the MACE (AUC 0.76 p<0.001) was not improved by combining with GRACE score (AUC 0.72 p<0.001) both (AUC 0.76 p<0.001). ROC analyses provided the optimum cut off value for MRproANP for prediction of MACE of 165 pmol/L which gave optimum survival stratification on Kaplan–Meier analysis (log rank 90.12 p<0.001). Conclusion: MRproANP level is a potent prognostic marker of adverse events. Admission levels offer early identification of high risk NSTE-ACS patients and its role in optimising management requires further investigation.